Analisis Faktor-Faktor yang Mempengaruhi penggunaan E-Wallet di Sumatera utara - Sukma Hayati Hakim; Arif Rahman; M. Syafii (Owner : Riset dan Jurnal Akuntansi, 2022)
The COVID-19 pandemic that has hit the world, including Indonesia, has had a very serious impact on all sectors. This also makes a real contribution to the very rapid progress of technological development. All activities that were previously usually carried out in person, but now have to be done virtually or online. So that internet-based technology that is always used by the community is the most efficient to use during this pandemic, including in terms of payment transactions. The increasing number of internet users, which continues to rise from year to year, especially during this pandemic has caused many internet-based applications. The application of digital technology in the economy is very clear, especially in the financial sector, which is called financial technology. One of the products of financial technology is mobile payment or also called e-wallet. The rise of e-commerce on various online platforms has also led to an increase in payments using e-wallet. This research was conducted to determine the extent of the use of e-wallet, among the community and the factors that influence it.